Considering African philosophy as a way of life through the practice of philosophical counselling - Louw, Jaco (South African journal of philosophy, 2025)
Contributions of Pierre Hadot pertaining to the notion of philosophy as a way of life have had a profound and enduring influence upon philosophical counselling. Philosophical counsellors, such as Robert Walsh and Arto Tukiainen, embrace this imperative by living their philosophical counselling practices. A prevailing trend among these practitioners lies in their almost exclusive reliance upon either ancient Greek philosophical traditions as expounded by Hadot and Martha Nussbaum, or in their adaptation of Western philosophy. Regrettably, a conspicuous omission prevails regarding the incorporation of contemporary African philosophy, notably their philosophical praxes as a way of life/living, within the philosophical counselling discourse. The integration of African philosophy into philosophical counselling holds significant promise, particularly concerning the potential to impact ways of living within a southern African context. Within the wider landscape of contemporary African philosophy, certain authors have already conceptualised Ubuntu philosophy as a way of life/living. Notwithstanding, I undertake to introduce two additional African philosophical practices, namely hermeneutic African philosophy and conversational philosophy. I advance a novel interpretation of both by positioning them as relevant praxes for philosophical counselling. Emphasis is placed on interpretative actualisations in response to lived experiences, contextualised within a conversational framework. The implications for philosophical counselling are threefold: first, there is a disclosing of alternative ways of living/becoming along with the creation of new concepts; second, the relational dimension of philosophising is emphasised; and third, methodological constraints concerning the practice of philosophical counselling are transcended while embracing the transformative potential of reflective, creative and critical conversations.